The management of culture : professional challenges of managing narratives and brands in a changing cultural environment - Gomes, Nelson Pinheiro (2017)
This paper explores the relations between culture, consumer behavior and management, introducing a new perspective for the study of cultural management, in order to activate better relationship strategies between brands and their audiences. The objective is to understand the instrumentalization of culture and behavior changes, resulting in a better creation and management of cultural symbols and narratives for brands. The ability to create and to imprint meanings in new products, services and pieces of communication requires a professional not only in the field of brand management, but also on the study of culture and emerging mindset and behavior trends. In this sense, this paper explores the role of this professional, the Chief Culture Officer (CCO), and how he/she can benefit from the application and the development of trends studies.